Penyelesaian Perkara Tindak Pidana Anak dan Tindak Pidana Ringan Dalam Sistem Peradilan Pidana Dengan Pendekatan Restorative Justice - Ama, Jefrianus Tamo (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Restorative justice is a new paradigm in the criminal justice system that focuses on restoring harm and social relationships caused by criminal acts, rather than merely punishing the offender. This study aims to examine the implementation of restorative justice in Indonesia, particularly in cases involving juvenile and minor offenses, using a normative juridical research methodology and literature study approach. The findings show that restorative justice is effective in preventing children from entering the formal justice system, reducing psychological impacts, and strengthening substantive justice values and local wisdom. Its implementation is supported by several legal frameworks, including Law No. 11 of 2012, Supreme Court Regulation (PERMA) No. 4 of 2014, and National Police Regulation (Perkap) No. 8 of 2021. However, challenges remain due to limited understanding among law enforcement officers, low public awareness, and inadequate facilities and infrastructure. Therefore, systemic support through officer training, public dissemination, and infrastructure enhancement is necessary to realize the principles of restoration, reconciliation, and shared responsibility effectively.